Mental Health in European Economics Departments - Elisa Macchi; Clara Sievert; Valentin Bolotnyy; Paul Barreira (Institute of Labor Economics (IZA), 2023)
We study the mental health of graduate students and faculty at 14 Economics departments in Europe. Using clinically validated surveys sent out in the fall of 2021, we find that 34.7% of graduate students experience moderate to severe symptoms of depression or anxiety and 17.3% report suicidal or self-harm ideation in a two-week period. Only 19.2% of students with significant symptoms are in treatment. 15.8% of faculty members experience moderate to severe depression or anxiety symptoms, with prevalence higher among non-tenure track (42.9%) and tenure track (31.4%) faculty than tenured (9.6%) faculty. We estimate that the COVID-19 pandemic accounts for about 74% of the higher prevalence of depression symptoms and 30% of the higher prevalence of anxiety symptoms in our European sample relative to a 2017 U.S. sample of economics graduate students. We also document issues in the work environment, including a high incidence of sexual harassment, and make recommendations for improvement.
Keywords: A23; I12; I18; I23; 330; student mental health; faculty mental health; wellbeing